The synovial grade corresponding to clinically involved joints and a feasible ultrasound-adjusted simple disease activity index for monitoring rheumatoid arthritis. Issue 6 (1st November 2016) - Yamada, Yusuke; Ogasawara, Michihiro; Gorai, Misa; Matsuki, Yuko; Murayama, Go; Sugisaki, Nagachika; Nemoto, Takuya; Ando, Seiichiro; Minowa, Kentaro; Nakano, Souichiro; Kon, Takayuki; Tada, Kurisu; et al.
Abstract: Objectives : To determine which grade of ultrasound (US) synovitis corresponds to clinically involved joints in rheumatoid arthritis (RA) and develops a new US-adjusted composite measure. Methods : Clinical and US examinations were performed on 137 patients with RA (28 joints). Synovial effusion, hypertrophy, and blood flow were semiquantitatively graded from 0 to 3 using gray scale (GS) and power Doppler (PD) modes. We calculated US-adjusted simple disease activity index (SDAI) and assessed feasibility, and external validity by comparing with erythrocyte sedimentation rate (ESR), and modified health assessment questionnaires (MHAQ). Results : GS ≥2 and PD ≥0 corresponds to clinically swollen joints, and GS ≥2 and PD ≥1 corresponds to tender joints. The US-adjusted SDAI showed the highest correlation when US-determined swollen joints were defined as PD ≥2 with ESR, and GS ≥3 and PD ≥2 with MHAQ. A feasible US-adjusted SDAI examining only clinically involved joints still showed a higher correlation with ESR and MHAQ than SDAI. Conclusion : Our composite measure complemented by US only for clinically involved joints is feasible and reliable for monitoring disease activity.